Incidencia de bajos niveles de daño foliar de Tuta absoluta (Meyrick) en tomate - Silva, E. B.=700 1 Mexia, A.
Resumenes (Es, En)
6 tab; 29 ref.
Keywords: LEPIDOPTERA; PYRALIDAE; PLANOCOCCUS CITRI; HOMOPTERA; PSEUDOCOCCIDAE; DINAMICA DE LA POBLACION; CITRUS SINENSIS; POLILLA DEL NARANJO; CRIPTOBLABES GNIDIELLA; COCHINILLAS; NARANJO DULCE; ASOCIACION INTERESPECIFICA